Engenharia de cristais: estudo supramolecular de 1-, 1,3-bis e 1,3,5-tris (carboxamida)benzenos contendo substituintes aminoácidos - Lima, Priscila Santos Vieira de (2024)
This thesis presents a study on the formation of the crystalline network of carboxamidebenzenes compounds in single crystals (crystalline solid state) and in solution. Six series of compounds carboxamidebenzenes: 1- carboxamidebenzenes, 1,3-bis(carboxamide)benzenes and 1,3,5-tris(carboxamide)benzenes were synthesized, with different terminal portions, being amino acids or amino esters. A supramolecular analysis was carried out using tools such as X-ray diffraction, theoretical DFT calculations and quantum theory of atoms in molecules (QTAIM), in which the types and energies of interactions involved in the molecules that make up the supramolecular cluster were determined. From the QTAIM analyses, it was observed that interactions of the CH···O type stood out as the predominant interactions for all substitution patterns, presenting a contribution greater than or approximate to that of the classical hydrogen interactions of the NH···O type. Furthermore, proposals for crystallization mechanisms were considered to identify the influence of substituents (amino acid/amino ester) and different substitution patterns on crystalline packing It was observed that the compounds derived from glycine (6a, 8a, 9a) present supramolecular differences even though they present molecular similarities. This same behavior is observed for compounds derived from alanine (4b, 5b, 7b and 9b). In order to corroborate the proposed crystallization mechanisms, concentration variation NMR experiments were used to verify the intermolecular interactions involved in the first stages of crystallization. Electrospray ionizations Mass Spectrometry (ESI-MS) experiments were performed to investigate the persistence of the supramolecular clusters in solution. In this way, the intermolecular interactions in the crystalline packing of carboxamidebenzenes compounds were analyzed considering the correlation of data in the crystalline solid state and in solution. Regarding the identification of the stereochemistry of the synthesized compounds, X-ray diffraction analyzes of the single crystals obtained indicated that the products synthesized from S- or R-amino acids presented a single configuration at the supramolecular level, while those obtained from RS-amino acid mixtures presented both “R,S” configurations in the supramolecular cluster. All compounds were characterized by one- and two-dimensional 1H and 13C Nuclear Magnetic Resonance (NMR) analyses.